Un aspecte del procés de modernització de la literatura catalana en el primer terç de segle - Balaguer, Josep Maria (Caplletra. Revista Internacional de Filologia, 2015)
This study examines how certain Catalan critics and poets valued and integrated an overall concept of Catalan poetry from the Valencian Country and the Balearic Islands. The analysis focuses on the Antologia de poetes catalans d'avui (1913), Antologia de poetes catalans moderns (1914) by A. Plana, Les noves valors de la poesia catalana (1919) by Joaquim Folguera, and the section dedicated to modern poetry in the Antologia general de la poesia catalana (1936) by Riquer, Miquel, and Vergés i Teixidor.